The Effect of Project Based Learning on the Entrepreneurial Skills of Eleventh Grade Culinary Students at SMKN 2 Bukittinggi - Muhammad Gilang Permana Putra; Cici Andriani; Ezi Anggraini; Wiwik Indrayeni (Universitas Negeri Padang, 2026)
This study aims to determine the effectiveness of the Project Based Learning model on the entrepreneurial skills of eleventh-grade Culinary students at SMKN 2 Bukittinggi. This research employed a quantitative method with a one-group pretest-posttest design. The subjects of this study consisted of 105 students. The instrument used was an entrepreneurial skills test administered before (pretest) and after (posttest) the implementation of the Project Based Learning model. The data were analyzed using normality test, homogeneity test, paired sample t-test, and N-Gain analysis.The results showed that the average pretest score was 67.25, categorized as moderate, while the average posttest score was 81.40, categorized as high. The paired sample t-test result indicated that the calculated t-value (12.85) was higher than the t-table value (1.98) with a significance value of 0.000 < 0.05, indicating a significant effect of the Project Based Learning model on students’ entrepreneurial skills. The N-Gain score of 0.43 was classified as moderate, indicating a moderate level of effectiveness.Based on these findings, it can be concluded that the Project Based Learning model is effective in improving the entrepreneurial skills of eleventh-grade Culinary students.